2008
DOI: 10.1590/s0006-87052008000100015
|View full text |Cite
|
Sign up to set email alerts
|

Controle genético da exigência térmica para o início do florescimento em milho

Abstract: GENETIC CONTROL OF THE THERMAL DEMAND FOR FLOWERING INITIATION IN MAIZEThe objective of this work was to study the genetic control of thermal demand for maize flowering initiation. Two contrasting lines were crossed and used with the F 1 , F 2 RC 1 and RC 2 derived populations. The trait day-degrees between sown and flowering per plant were evaluated to obtain the estimates of components of variance and means. All models of mean components had R 2 values near 100%, and then the simple additive-dominant model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(3 reference statements)
1
3
0
1
Order By: Relevance
“…Estimation for the number of effective factors (EF) showed that all of the investigated flowering traits were controlled by few genes (Table 3). This finding is similar to the results of previous studies (Lima et al 2008). Lopes et al (1995) reported that gene number (effective factor) for flowering traits varied from one to nineteen in the different studies.…”
Section: Resultssupporting
confidence: 93%
“…Estimation for the number of effective factors (EF) showed that all of the investigated flowering traits were controlled by few genes (Table 3). This finding is similar to the results of previous studies (Lima et al 2008). Lopes et al (1995) reported that gene number (effective factor) for flowering traits varied from one to nineteen in the different studies.…”
Section: Resultssupporting
confidence: 93%
“…Studies of other cultures prove that the air temperature influences the flower anthesis, both complete or unisexual flowers, such as in Zea mays (Lima et al, 2008) and in Gladiolus × grandiflorus (Streck et al, 2012). The accumulated thermal sum also reported as thermal constant, has been widely used to determine the time necessary to the anthesis of flowers in various vegetables (Volpe et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…O milho (Zea mays L.), originário da América Central, é uma gramínea pertencente à família das Poaceas, e uma das plantas mais eficientes produtoras de energia na natureza, em virtude a sua vasta capacidade de acumular fotoassimilados. É uma planta monoica, isto é, contém órgãos femininos e masculinos separados, no entanto ficam na mesma planta (LIMA, 2006). Amplamente disseminada no território brasileiro, a cultura do milho é de grande importância econômica, social e vasto potencial produtivo.…”
Section: Introductionunclassified